Influence of Role Models and Mentors on Female Graduate Students’ Choice of Science as a Career (Alberta Journal of Educational Research, 2010)
The purpose of this study was to examine the source, nature, and degree of influence of role models and mentors on female graduate students’ choice of science as a career. Also examined was the existence of gender or area-of-study (engineering, biological science, physical sciences) differences. Results of a factor analysis of the Influence of Others on Academic and Career Decisions Scale (IOACDS, Nauta & Kokaly, 2001) demonstrated that role models and mentors influenced students in distinct ways. Significant gender, area-of-study, and undergraduate country differences were found.